Entanglement and statistical properties in cavity optomechanics with a single atom. (11th April 2019) - Xu, Ye-Jun; Wang, Shuang-Shuang; Chen, Meng-Ran; Liao, Qing-Hong
Abstract: We put forward a proposal to prepare tripartite interplay in a cavity optomechanical system with a two-level atom. We study the dynamical properties of the atomic linear entropy and find that the entanglement between the atom and the subsystem of the field and mechanical resonator can be effectively manipulated by atom coherence. The Mandel parameter is employed to reveal the sub-Poissonian statistics of the optical and mechanical modes. Moreover, we discuss the influence of the system dissipations, including atomic, optical and mechanical modes, on the temporal evolution of the linear entropy and the Mandel parameters.